Continuing Pharmacy Education: Effect on Knowledge, Attitude and Practice of Community Pharmacists in South India - Durai, Raja; Swaminathan, Krishna Kumar; Krishnamoorthy, Alam; Stephen, Salomi; Babu, Nivetha Chellapathy; Pandey, Adarsh; Chandrashekar, Keerthana; Sivasankaran, Ponnusankar (Indian Journal of Pharmacy Practice)
Background: Community pharmacists are healthcare professionals who play a major role in providing health care services. Continuing pharmacy education modules are designed to update the pharmacists' knowledge and skill to improve their practice. Objectives: This study was performed to evaluate the influence of continuing pharmacy education on pharmacist knowledge, attitude and practice towards 3 diseases viz diabetes mellitus, hypertension and peptic ulcer disease in selected districts of Kerala and Tamilnadu in South India. Method: A prospective open label study was performed among the community pharmacists in selected; 6 districts of Kerala and 4 districts in Tamilnadu over a period of 18 months from July 2013 to December 2014. The prepared course content for the diseases was provided to community pharmacist. The Knowledge, Attitude and Practice (KAP) were assessed by a questionnaire at baseline and post CPE follow up. The feedback for the lecture modules was taken. Statistical analysis was done by using GraphPad Prism Statistical Software version 6.02 and SPSS version 22 for windows. Results: Among 156 from Kerala and 157 community pharmacists from Tamilnadu, as per the protocol only 60 (38.46%) community pharmacists and 53 (33.76%) completed the study in Kerala and Tamilnadu respectively. Among them 62.83% (n=71) were male, 69.02% (n=78) were B. Pharm degree holders and 30.97% (n= 35) were diploma in pharmacy holders respectively. The baseline score for Knowledge, Attitude and Practice (KAP) were 33.78 (Kerala), and 32.25 (Tamilnadu) respectively. Statistically significant improvement in Knowledge, Attitude and Practice scores were found at the end of the study. Conclusion: The specified continuing pharmacy education program made a significant change (P<0.0001) in pharmacist’s knowledge, attitude and practice. The Community pharmacist gave a satisfactory score in feedback for the lectures delivered.
Keywords: Continuing pharmacy education; community pharmacist; knowledge; attitude; practice; lectures